2020
DOI: 10.1021/acsami.0c19595
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Deposited Anisotropic Ferromagnetic Hybrid Polymer Films of PS-b-PMMA and Strontium Hexaferrite Magnetic Nanoplatelets

Abstract: Spray deposition is a scalable and cost-effective technique for the fabrication of magnetic hybrid films containing diblock copolymers (DBCs) and magnetic nanoparticles. However, it is challenging to obtain spray-deposited anisotropic magnetic hybrid films without using external magnetic fields. In the present work, spray deposition is applied to prepare perpendicular anisotropic magnetic hybrid films by controlling the orientation of strontium hexaferrite nanoplatelets inside ultra-high-molecular-weight DBC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 66 publications
0
23
1
Order By: Relevance
“…Such increased order of the DBC structure in the hybrid film originates from the reduced number of parallel PMMA cylinders (as seen in SEM) due to the addition of the FePt NPs. The more parallel PMMA cylinders are present, the more they disturb the DBC structure, [ 17 ] because they are distributed in the film with random orientations (Figure 1). With further increasing time, again an increase in the error bars of feature I is observed (from 12.6 to 33.6 s, marked with semi‐transparent colors in Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such increased order of the DBC structure in the hybrid film originates from the reduced number of parallel PMMA cylinders (as seen in SEM) due to the addition of the FePt NPs. The more parallel PMMA cylinders are present, the more they disturb the DBC structure, [ 17 ] because they are distributed in the film with random orientations (Figure 1). With further increasing time, again an increase in the error bars of feature I is observed (from 12.6 to 33.6 s, marked with semi‐transparent colors in Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, various methods, like spin coating, spray coating, and printing, were utilized to prepare magnetic NP-DBC films with different morphologies and magnetic properties. [15][16][17] Among these fabrication methods, printing has obtained increasing attention because of its large-scale production capability in industrial applications. [15,18,19] Moreover, printing is an effective method to obtain homogeneous films with smooth surfaces on a macroscopic level compared to other methods such as spray coating.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recently, numerous attempts were made to further enhance/improve the magnetic properties of the SFO by metal ion doping, adopting suitable synthesis methods, and optimizing the processing conditions. 2 15 Also, composites of SFO with soft magnetic phases and improved magnetic properties achieved through the exchange-spin mechanism have been reported in the literature. 3 , 10 , 16 , 17 For instance, using a conducting polymer and a SFO content for tunability, polypyrrole/SFO composites were designed and tested for efficient EM-shielding purposes.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Most recently, magnetic hybrid films containing diblock copolymers (DBCs) and magnetic NPs of SFO were also considered for sensor applications. 2 Spray deposition was applied to prepare perpendicular anisotropic magnetic hybrid films by controlling the orientation of SFO nanoplatelets inside ultra-high-molecular-weight DBC polystyrene- block -poly(methyl methacrylate) (PS- b -PMMA) films. 2 Using the superconducting quantum interference device data, authors demonstrated that the ferromagnetic hybrid polymer films with high coercivity can be achieved via spray deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation